Strategies for Introducing West Kalimantan’s Local Culture through the Sinema Mikro Program - Bob Andrian; Haris Supiandi; Lulu Hendra Komara; Rokhmadi (Mediakita, 2026)
This study examines the preservation of West Kalimantan’s local culture through the Sinema Mikro Program by the Siberdaya Galang Sinergi Community, focusing on film screenings and culturally themed discussions in coastal and island areas. This issue is significant because globalization shifts the younger generation’s attention from local cultural identity, necessitating innovative strategies to maintain cultural existence. The research aims to analyze the effectiveness of Sinema Mikro in introducing and preserving local cultural values, and to design more effective strategies. A qualitative method with an ethnographic approach was employed, involving participatory observation, in-depth interviews, and domain-theme analysis at six screening locations (Lemukutan, Kabung, Temajuk, Tayan, Karimata, Batu Ampar). The results showed that film screening combined with participatory discussions improved cultural understanding, social interaction, and dialogue, although community responses varied according to socio-economic conditions, accessibility, and demographics. In conclusion, the program is effective in expanding cultural literacy in remote areas and is recommended for developing context-based local programs, as well as for advanced research to measure long-term impacts and support the advancement of national culture.